Synthesis, characterization and photo-electrochemical properties of novel Cu(Cr1-x, Alx)2O4 spinel oxides for enhanced photodegradation of organic dyes under UV light. (19th February 2022) - Bahdaouia, Asma; Amara, Sifeddine; Adnane, Leïla; Columbus, Soumya; Daoudi, Kais; Mahieddine, Abdelkadir
Abstract: In the present work, physical, photo-electrochemical properties and photocatalytic activity of Cu(Cr1- x, Al x )2 O4 ( x = 0, 0.1, 0.5, 0.9 and 1) spinels synthesized via the nitrate route were investigated for the first time. X-ray diffraction (XRD) with Rietveld refinement confirms the purity of all samples while SEM images show the porous and spongious morphology of the oxides of 62–311 nm grain sizes. The chemical composition and the oxidation states were determined by X-ray photoelectron spectroscopy (XPS) analysis. The specific surface area is highly affected by x -ratio. The photoelectrochemical behavior of the synthesized materials was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Mott-Schottky in Na2 SO4 electrolyte (0.1 M). Indeed, the electrochemical tests under the effect of light show an increase in the current intensity and a decrease in the charge transfer resistance in CV and EIS tests, respectively. These materials were applied as photocatalysts for the photodegradation of Methylene Blue (MB) under UV light with the aid of H2 O2 serving as generator of free radicals. Our results show that Cu(Cr0.1, Al0.9 )2 O4 is the most performant photocatalyst of MB with a degradation efficiency of 98.8% within 80 min of irradiation. Furthermore, the photocatalytic activities of Cu(Cr0.1, Al0.9 )2 O4 were evaluated by the degradation of Rhodamine B (RhB) and Methyl Orange (MO) and the results reveal a good performance toward RhB degradation (85.5%), and to a lesser degree for MO decomposition (67.3%). Graphical abstract: Image 1 Highlights: Cu(Cr1- x, Al x )2 O4 oxides are synthesized by nitrate reaction for the first time. Physicochemical properties and photocatalytic activity are investigated. Efficient degradation of the dye within 10 min of irradiation up to 96.36%. Cu(Cr0.1, Al0.9 )2 O4 is the most performant photocatalyst of MB degradation (98.8%). Efficient decomposition of RhB and MO by Cu(Cr0.1, Al0.9 )2 O4 .